Pengaruh Outbound Low Impact Terhadap Kerjasama Anak TK Katimpun Palangka Raya - Martono, Wahyuni Christiany (Journal Pendidikan Ilmu Pengetahuan Sosial, 2016)
This research is based by the importance of improving children's teamwork ability through low impact outbound activities. Outbound low impact is the kind of play activities that have little risk, these activities can use of a tool from school environment or can do it yourself (DIY). The purpose of this study was to investigate the influence of outbound low impact on the teamwork of kindergarten children Katimpun Palangkaraya. This research is quantitative research with experimental approach. The research sample are 17 children in group B TK Katimpun Palangkaraya Academic Year 2014/2015. Calculation of data using SPSS 17 (Statistical Product and Service Solution) uses Wilcoxon Match Pairs Test. The result is low impact outbound influence on the teamwork of children. This is evidenced by SPSS output using the Wilcoxon Match Pairs Test.